Prescribing Patterns and Polypharmacy in Renal-Impaired Patients: Insights from a Cross-Sectional Study in a Tertiary Care Hospital (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Chronic kidney disease (CKD) and renal impairment represent a growing global health challenge, contributing substantially to morbidity, mortality, and healthcare costs. The coexistence of comorbidities such as hypertension, diabetes, and anemia often necessitates multidrug regimens, thereby amplifying the risk of polypharmacy and inappropriate prescribing. Understanding prescribing trends in this vulnerable population is critical to advancing rational drug use and improving patient outcomes. Objective: To systematically evaluate prescribing patterns and quantify the burden of polypharmacy among renal-impaired patients in a tertiary care teaching hospital. Materials and Methods: A six-month, cross-sectional observational study was conducted involving 150 patients who met strict inclusion criteria. Data were meticulously collected through patient interviews, prescription audits, case records, and laboratory reports. Drug utilization was analyzed with respect to demographic variables, comorbidities, and therapeutic categories. Results: Of the 150 patients, 94 (63%) were male and 56 (37%) female, with the majority aged >60 years (39.3%). Anemia (95%), hypertension (86%), and diabetes mellitus (43%) were the most prevalent comorbidities. A total of 1,693 medications were prescribed, averaging 11.19 ± 3.51 drugs per patient, confirming universal polypharmacy. Cardiovascular agents (25.87%) dominated prescriptions, followed by gastrointestinal drugs (18.72%), vitamins/minerals (14.94%), and antibiotics (8.33%). The prescribing pattern highlights both the therapeutic complexity and the pressing need for evidence-based rationalization. Conclusion: Polypharmacy is ubiquitous among renal-impaired patients, driven by the burden of multiple comorbidities. The predominance of antihypertensive, gastrointestinal agents, antibiotics, and antidiabetic drugs underscores the necessity of stringent prescribing guidelines, clinical pharmacist interventions, and continuous drug utilization review. This study provides actionable insights to optimize therapeutic strategies, reduce medication errors, and enhance patient safety in CKD management.
Keywords: Chronic Kidney Disease; Polypharmacy; Prescribing Trends; Drug Utilization; Rational Pharmacotherapy